Forest Stewardship: Deforestation Analyzed Islamecocritically in Canadian Ecopoetry - Inas Samy Abolfotoh (Al-Jami'ah: Journal of Islamic Studies, 2022)
Deforestation is one of the current global hot issues. It has a complicated web of causes and effects. Besides, it requires intricate long-term solutions because many countries are involved. The present study presents an Islamecocritical reading of deforestation causes, effects, and solutions. The literary discussion is combined with religion and science through analyzing selected Canadian poems in reference to Islamic doctrines and scientific facts. The concept of forest stewardship is highlighted as a worldwide demand for handling this issue. Forest stewardship is definitely tied to other fundamental Islamecocritical principles like moderation; corruption prohibition; harm prevention; innateness; animism; the unity principle; heavenly balance; and divine judgment. These ethical pillars are supposed to guarantee the wished-for harmonious responsible relationship between humans and forests. [Deforestasi merupakan salah satu isu penting global saat ini. Hal ini seperti jaring kompleksitas dari sebab dan akibat. Disamping itu, persoalan ini membutuhkan solusi jangka panjang karena melibatkan banyak negara. Artikel ini membahas pembacaan ekokritisme Islam pada sebab, akibat dan solusi dari deforestasi. Literasi diskusi adalah kombinasi agama dan sains melalui analisa puisi dari Kanada yang terkait dengan doktrin Islam dan fakta sains. Konsep pelestarian hutan menjadi sorotan yang lebih luas dalam mengatasi persoalan ini. Pelestarian hutan menjadi pengikat pasti dari prinsip dasar ekokritis Islam seperti: pencegahan korupsi, anti kekerasan, pembawaan, animisme, kesatuan, keseimbangan, dan keadilan Tuhan. Pilar pilar etik inilah yang kira-kira menjamin hubungan harmonis antara manusia dan hutan.]